Public knowledge about modifiable risk factors of dementia in Iceland - Stefanía Ýr Hannesdóttir 1999- (2021)
Public knowledge about modifiable risk factors for dementia is vital. People can use that knowledge to take better care of themselves and by doing so they are reducing the chances of getting dementia in the future. The aim of this study was to examine general knowledge on dementia and knowledge on modifiable risk factors of dementia. The sample was 829 participants from Iceland from 25-65 years old. The participants were collected by using a random sample from the National Register of Iceland. Likert scale questionnaires and multiple response questions were used to assess knowledge of modifiable risk factors. The results showed that: 1) There was a significant gender difference in knowledge about modifiable risk factors and symptoms of dementia. 2) Participants with higher level of education scored higher than those who had secondary education or less. 3) Participants that were in the age groups 25-34 and 35-44 years old had the highest knowledge on modifiable risk factors of dementia. 4) There was a difference between modifiable risk factors and knowledge varied by area if residence. Keywords: Dementia, Public Knowledge, Modifiable Risk Factors, Education, Age, Almenn þekking á áhættu- og verndandi þáttum heilabilunar er mikilvæg. Einstaklingar geta notað þessa þekkingu til að hugsa betur um sjálfa sig og með því draga þessir einstaklingar úr líkum á að fá heilabilun í framtíðinni. Markmið þessarar rannsóknar var að skoða almenna þekkingu á heilabilun og þekkingu á áhættu- og verndandi þáttum heilabilunar. Úrtakið var 829 þátttakendur frá Íslandi frá aldrinum 25-65 ára. Þátttakendum var safnað með því að nota slembiúrtak úr Þjóðskrá Íslands. Notaðir voru spurningalistar af Lickert skala og sammála og ósammála spurningar til að meta þekkingu á áhættu- og verndandi þáttum. Niðurstöðurnar sýndu að: 1) Marktækur munur á þekkingu á áhættu- og vernandi þáttum þáttum og einkennum heilabilunar eftir kyni. 2) Þátttakendur með meiri menntun skoruðu hærra en þeir sem höfðu framhaldsskólagráðu eða minna. 3) Þátttakendur ...